ß2-adrenoceptor polymorphisms predict response to ß2-agonists in children with acute asthma - Martin, A.; Zhang, Guicheng; Rueter, K.; Khoo, S.; Bizzintino, J.; Hayden, C.; Geelhoed, G.; Goldblatt, J.; Laing, I.; Le Souëf, P. (Informa Healthcare, 2008)
The aim of this study was to determine the influence of single nucleotide polymorphisms in the ß2-adrenoceptor gene, on the response to inhaled ß2-agonists in children with acute asthma. We hypothesised that children with polymorphisms that generate enhanced receptor downregulation in vitro, Gly16 and Gln27, would have a slower response to ß2-agonist therapy during acute asthma. One hundred and forty-eight children with acute asthma were recruited and genotyped for ß2Arg16Gly and ß2Gln27Glu. For Gln27Glu, individuals Gln27Gln took longest to stretch out to 1, 2 and 4 hourly ß2-agonists, followed by heterozygotes who were intermediate and Glu27Glu who responded most rapidly (1hourly: 2.6hr vs. 2.0 vs. 1.4, p = 0.02; 2 hourly: 10.6hr vs. 10.7 vs. 6.8, p = 0.07; 4 hourly: 29.8hr vs. 28.5 vs. 24.3, p = 0.30). The ability to prospectively identify children who respond less effectively to ß 2-agonists during an acute asthma attack has the potential to allow the generation of genotype-specific treatment pathways. Copyright © 2008 Informa Healthcare USA, Inc.